Preparing students for a changing world: how geography curricula in Europe are tackling climate change - Enke, Klaas Alexander; Budke, Alexandra (Frontiers in Education, 2023)
Climate change education has gained attention in recent years, with curriculum analyses conducted primarily at the national level. However, a comparative analysis of implementation in different European countries is still lacking. This study aims to address this research gap by comparatively examining the geography curricula of France, Spain, Germany, and Italy. The analysis reveals differences in the inclusion of physical-geographical content related to climate change. Likewise, the emphasis on either the natural or the socio-economic effects of climate change varies across the countries. All curricula include concrete competencies and learning objectives for climate education, but a gap is visible in social learning objectives. The analysis highlights the importance of exchanging best practices an experiences among European countries.